Mind the Gap - Espen Beer Prydz; Dean Jolliffe; Umar Serajuddin (Global Labor Organization (GLO), 2021)
Estimates of average per capita consumption and income from national accounts differ substantially from corresponding measures of consumption and income from household surveys. Using a new compilation of more than 2,000 household surveys matched to national accounts data, we find that the gaps between the data sources are larger and more robust than previously established. Means of household consumption estimated from surveys are, on average, 20 percent lower than corresponding means from national accounts. The gap with GDP per capita is nearly 50 percent. The gaps have increased in recent decades and are largest in middle-income countries, where annualized growth rates for consumption surveys are systematically lower than national accounts growth rates. We show that the gaps in measures across these two sources have implications for assessments of economic growth, poverty, and inequality. We find that typical survey measures of consumption and income may exaggerate poverty reduction and underestimate inequality.
Keywords: I3; I32; E31; F01; 330; National Accounts Systems; Household Income and Expenditure Surveys; Poverty; Inequality